Profil Strength of Hope Mahasiswa Calon Guru BK Berdasarkan Faktor Budaya - Hartanto, Dody (Departemen Psikologi Pendidikan dan Bimbingan FIP Universitas Pendidikan Indonesia, 2017)
Hope is a construct that has been revealed and investigated in the process across space and time. Hope as an important aspect in the development and lives of individuals known to correlate with various factors, but have not revealed many factors related to culture, especially in Indonesia. This study aims to reveal the expectations on students of Guidance and Counseling Study Programme FKIP UAD Special Region of Yogyakarta Indonesia. The study was conducted on 123 students of VII semester consisting of 45 men and 78 women. The average age of study participants was 20-22 years old. The instrument used is the Hope Scale, shaped semantic differential scale that is composed of a large selection of 1-8 (1 = very inappropriate, and 8 = very appropriate). Descriptive statistical data analysis used in this study. Results of the study showed no significant difference in the expectations of students are female than male. In the dimension measurement known student agency in Guidance and Counseling Study Programme higher than pathways dimension. Hope Sundanese cultural background of students is the highest and the lowest was followed Javanese students who have a background in Malay culture. While the expectations of the most frequently encountered are related to career, parents and self-oriented (individualism).